UV therapy: Physiotherapists' perception of therapeutic efficacy and barriers to usage - Jibril Mohammed Nuhu, MSc; Jibril Mohammed, MSc; Mubarak Muhammad, B Physiotherapy (World Scientific Publishing, 2014)
This study was conducted to assess the perception of efficacy of ultraviolet (UV) light therapy and barriers to its use among physiotherapists. A purpose-designed questionnaire containing 29 items, seeking information on perception of efficacy of UV therapy and perceived barriers to its use, was administered to physiotherapists in Northwestern Nigeria. With a response rate of 97%, it was demonstrated that almost 70% of the respondents perceived UV therapy to be effective and only 59.3% of them had ever used UV therapy for treatment purposes. In general, the major barrier to the use of the modality was nonavailability of UV therapy machine (66.1%) followed by availability of a substitute treatment modality (13.5%). Lack of referral of patients with indications for possible use of UV therapy accounted for 10.2%. The study also found significant association between the use of UV therapy by the respondents and the perception of its therapeutic efficacy (p < 0.05), and perception of the modality as being abandoned by physiotherapists (p < 0.05). It was concluded that despite the low level of use of UV therapy mainly due to its unavailability, physiotherapists in Northwestern Nigeria perceived the modality as being efficacious.